2020
DOI: 10.1177/0040517520920949
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic modeling approach for a high-speed winding system with twin-rotor coupling

Abstract: This paper continues the previous study and presents a dynamic modeling approach for a high-speed winding system. To meet the requirements of high-speed winding, a twin-rotor coupling structure is adopted in the winding system. It is a complex spindle system, due to its high speed, heavy load, frequency-dependent coupling parameters, and time-varying rotational speed. In this paper, an approach to establishing a finite element model of the winding system is proposed to predict its dynamic behavior characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…However, the experiment results and literature values still had differences, which could be caused by the different packages' density, winding tension, the filament type, the contact roller's diameter, and so on. Moreover, the results of the equivalent contact stiffness in this article are in agreement with Hou et al, 5 but the values are greater than the literature values. That is because the equivalent radial Young's modulus of the package of the literature is a constant.…”
Section: Correctness and Effectiveness Combining Experiments And Simulationsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the experiment results and literature values still had differences, which could be caused by the different packages' density, winding tension, the filament type, the contact roller's diameter, and so on. Moreover, the results of the equivalent contact stiffness in this article are in agreement with Hou et al, 5 but the values are greater than the literature values. That is because the equivalent radial Young's modulus of the package of the literature is a constant.…”
Section: Correctness and Effectiveness Combining Experiments And Simulationsupporting
confidence: 91%
“…Winding regularities of the high-speed winding system are shown in Figure 3. 5 Spindle rotation speed means the rotation speed of the spindle and the packages in the winding process from empty to full package.…”
Section: Winding Regularities Of the High-speed Winding Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] For the winding of the polyester filament, Wang et al 1 carried out finite element modeling and dynamic analysis for the complex twin-rotor system of the high-speed winder, aimed to enable the spindle to be smoothly wound according to the requirements of speed changes during the winding. Hou et al 6 established the dynamic model of the twin-rotor system formed by the contact roller and the package. Hou et al's work also showed that the formation of the package and the precise placement of the polyester filament are the focus of the winding system.…”
mentioning
confidence: 99%